Utilização de cateter central de inserção periférica em pacientes adultos: percepções de enfermeiros - Costa, Letícia Machado da (2015)
The peripherally inserted central catheter (PICC) is a catheter that is inserted in a peripheral vein, which get along to the superior or inferior cava vein, getting in a central localization, which promotes more safety and comfort to patients. A trained nurse, according to the Resolution of the Federal Nursing Council n º, inserts this catheter. 258/2001. The general objective of this study was aimed to know nurses‟ perceptions when using the peripherally inserted central catheter on adult patients at a teaching hospital. The specific objectives were: to describe nurses‟ experiences in relation to the using of peripherally inserted central catheter on adult patients; and to identify the facilitating and complicating factors in relation to the use of peripherally inserted central catheter by nurses. The research constituted a qualitative, descriptive and exploratory study. The place of study was the Teaching Hospital of Santa Maria, specifically, at areas of adult patients. Data collection was carried out from May to August of 2015. The participants of study were 18 nurses who had training for peripherally inserted central catheter and worked with adult patients. Data was collected through semistructured interviews, which were recorded via audio and later transcribed. Data was also analyzed through thematic analysis. The ethical aspects according to the Resolution 466 of December 2012 from the National Health Council were respected, and the project approved by the Ethics Research Committee under the number CAAE 40675915.1.0000.5346. from the results, three categories emerged: the trained nurses‟ experience when using the peripherally inserted central catheter on adult patients; aspects that interfere when using peripherally inserted central catheter on adult patients; and the using of peripherally inserted central catheter by trained nurses on adult patients: seeking for autonomy. It was possible to verify that the nurses‟ experience when using this catheter on adult patients is recent and timorous. The interviewers cited as facilitating factors for using the catheter: stimulus from the institution, availability of catheter and the support of medical and nursing teams. On the other hand, the complicating factors were: few trained nurses; lack of divulgation of people that have the training; lack of training of nursing professionals; lack of people and time to insert the catheter; service characteristics, patients‟ profile and type of treatment; venous system of hard access; ultrasound machine missing; being a teaching hospital; lack of knowledge from medical and nursing teams; and the lack of eye of nurses to diagnose the necessity of catheter insertion. The results evidenced that PICC is seen as the last option for venous access for some nurses and physicians, being almost not used due to the lack of knowledge between medical and nursing teams. Thus, the nurse has a fundamental role when seeking to upgrade and update their knowledge on the catheter, having to remember their autonomy in order to amplify the using of PICC on adult patients. For this reason, he/she needs to be proactive, have a critical and reflexive thinking to evaluate the patient as soon as he gets into the Unity for earlier indication for this dispositive and train the team to use the same.